Reassessment of areas with persistent Lymphatic Filariasis nine years after cessation of mass drug administration in Sri Lanka. - Ramakrishna U Rao; Sandhya D Samarasekera; Kumara C Nagodavithana; Tharanga D M Dassanayaka; Manjula W Punchihewa; Udaya S B Ranasinghe; Gary J Weil (Public Library of Science (PLoS), 2017)
Sri Lanka was one of the first countries to initiate a lymphatic filariasis (LF) elimination program based on WHO guidelines. The Anti-Filariasis Campaign provided 5 annual rounds of mass drug administration (MDA) with diethylcarbamazine plus albendazole in all 8 endemic districts from 2002-2006. Microfilaremia (Mf) prevalences have been consistently <1% in all sentinel and spot-check sites since 2006, and all evaluation units passed school-based transmission assessment surveys (TAS) in 2013. We previously reported results from comprehensive surveillance studies conducted in 2011-2013 that documented low-level persistence of Wuchereria bancrofti in 19 high risk areas in 8 endemic districts. We now present results from repeat surveys conducted 3 to 4 years later in 6 areas that had the strongest LF signals in the prior study.The surveys assessed prevalence of filarial antigenemia (CFA) and Mf in communities, CFA and anti-filarial antibody in school children (ages 6-8), and filarial DNA in Culex mosquitoes (molecular xenomonitoring, MX). Three study areas had significantly improved infection parameters compared to the prior study, but three other areas had little change. MX was more sensitive for detecting W. bancrofti persistence, and it was a better predictor than other parameters. Adult males accounted for more than 80% of infections detected in the study.These results suggest that W. bancrofti transmission was near the break point in some of the areas studied in 2011-13. LF is likely to decline to zero without further intervention in these areas, while other areas may require further intervention. Long term surveillance may be needed to verify W. bancrofti elimination in areas like Sri Lanka with efficient transmission by Culex. Test and treat or other programs targeting adult males plus bed net promotion may be more effective than MDA for clearing remaining hotspots of transmission in Sri Lanka.